Reality Check: Insights on Critical Thinking in Health Education Through Mobile Mixed Reality - Stretton, Todd; Cochrane, Thomas (Australasian Society for Computers in Learning in Tertiary Education, 2023)
Mobile mixed reality (mMR) is increasingly being integrated into health education, however, the affordances and design principles for the facilitation of critical thinking are yet to be explored. The objective of this study is to explore the perceptions of mobile mixed reality and critical thinking in health education. Thematic analysis was undertaken of data collected from focus groups including students, academics, and mobile mixed developers (n=8). The focus groups revealed two main themes: (1) “purposeful critical thinking” including the benefits of freedom of failure in the virtual environment, and (2) “making it meaningful” by incorporating co-design of virtual learning environments while extending or focusing the learning experience to something that could not be achieved any other way. We conclude that the potential for mMR in health education is considerable. Purposeful inclusion of critical thinking could be achieved by students co-designing scenarios that integrate choose-your-own-adventure healthcare pathways in safe, virtual environments.
Keywords: mixed reality; mobile learning; critical thinking; authentic learning; co-design; health